LEGAL PROTECTION AGAINST CONSUMER BUYING ONLINE IN REVIEW FROM THE PERSPECTIVE OF LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - adminjfh, adminjfh (Fakultas Hukum Universitas Selamat Sri, 2022)
The development of information technology has changed people's habits in buying and selling transactions. Online transactions are a new way of conducting buying and selling activities by utilizing advances in information technology. Online transactions are developing in the community as a result of technological developments. The formulation of the problem in this study is how to protect the rights of online buying and selling consumers, how is the legal protection of online buying and selling consumers in terms of the Perspective of Law No. 8 of 1999 concerning Consumer Protection. The research used is this type of research. This scientific research uses normative legal research methods, including: research on various legal principles, research on legal synchronization levels, research on legal systematics, historical research, law, and legal comparative research. Law Number 8 of 1999 concerning Consumer Protection regulates consumer rights, in Article 4 there are eight rights that are explicitly explained while one last right is formulated openly.